EL PRINCIPIO DE PROPORCIONALIDAD EN LA JUSTICIA ORDINARIA Y TRANSICIONAL (2019)
In modern constitutionalism a series of principles have emerged, tending to develop the substantive nature of the higher norms and, within them, the preponderance that has acquired the principle of proportionality, which in penal matters allows to establish adequately the minimum and maximum limits of penalties, is unquestionable. being also, the main criterion to define the penalty in the concrete case; likewise, the aforementioned principle allows establishing a differentiated application of sentences in ordinary and transitional justice, noting that in the latter, restorative justice is privileged over retributive justice. In this regard, the application of the principle of proportionality is essential both in the legislative phase and at the time of the judicial application of the penalty; therefore, the amount of these should not exceed the magnitude of the seriousness that for society represents the punishable act that is sanctioned, and in parallel the establishment and imposition of derisory penalties, seriously violate the aforementioned principle; which, however, admits exceptions in transitional justice processes through which it intends to integrate various efforts in order to face the consequences of massive violations and widespread or systematic human rights abuses, suffered in the development of an armed conflict, with the purpose of building paths of peace, respect, reconciliation and consolidation of democracy; it is precisely for this reason that the application of the aforementioned principle in legislative processes and in legal and administrative proceedings acquires a huge preponderance, because if the essential postulates that stem from this principle are not met, there will be no truth, nor justice, nor proportional reparation and therefore, it will not be fulfilling the duty of peace and will not enjoy this such right.